PENGARUH PEMBERIAN MAKANAN TAMBAHAN PEMULIHAN TERHADAP PERUBAHAN STATUS GIZI BALITA GIZI BURUK DI TFC-FAJAR UPTD PUSKESMAS SAIGON KOTA PONTIANAK TAHUN 2018 - Andi Ipaljri Saputra; Sukma Sahreni (Jurnal Penelitian Keperawatan Medik, 2019)
Background: The best indicator to measure the nutritional status of the community is through the nutritional status of children under five. In an effort to overcome the problem of malnutrition in infants, the Ministry of Health of the Republic of Indonesia established a comprehensive policy, including prevention, promotion or education and management of malnutrition toddlers. The prevention efforts are carried out through growth monitoring in integrated service posts while malnourished children under five are treated with supplementary recovery feeding programs. Method: This research is a Quasi Experiment study with one group pretest and posttest design. The sampling technique was a total sampling with a sample of 32 patients. Univariate analysis was presented in the frequency distribution table and bivariate analysis using Spearman Rank Correlation test. Result: There was a significant influence on the nutritional status of children under five before and after PMT-P based on the weight-for-height index and weight-for-age. For the height-for-age index there was no significant influence on the nutritional status of children under five before and after PMT-P which means there was no correlation of the height-for-age index against PMT-P. Conclusion: There is a significant influence on the nutritional status of children under five based on the weight-for-height index and weight-for-age before and after PMT-P, but it is not related to the nutritional status of children under five based on the height-for-age index.